Core versus periphery: Examining the spatial patterns of insufficient accessibility in U.S. metropolitan areas. (April 2022) - Singer, Matan E.; Cohen-Zada, Aviv L.; Martens, Karel
Abstract: Recent transport equity literature suggests that accessibility analyses should move beyond mapping of the uneven patterns of access to opportunities. Instead, this literature proposes a sufficientarian approach, according to which all individuals are entitled to a minimum level of accessibility. In line with this approach, in this paper we ask: "What are the spatial patterns of accessibility insufficiency in U.S. metropolitan areas?" We use the Accessibility Fairness Index developed by Martens (Martens, K., 2017. Transport justice: Designing fair transportation systems. Routledge) and others to measure accessibility insufficiency. This index accounts for both people's accessibility shortfall compared to a sufficiency threshold and the number of people affected by these shortfalls. We limit our analysis to 49 of the 50 largest U.S. metropolitan areas and to people particularly reliant on transit, as they are especially likely to experience insufficient accessibility. We analyze first the spatial patterns of accessibility insufficiency for all 49 metropolitan areas jointly, for sufficiency thresholds ranging from 1% to 50% of average regional car-based accessibility. We find that accessibility insufficiency among people relying on transit is strongly concentrated in the first 10–30 km ring around the metropolitan core, with a more dispersed pattern only prevalent for the lowest 1% threshold. Next, we compare the 49 regions using only the 10% sufficiency threshold. Results show that most regions have a strong concentration of accessibility insufficiency in the urban cores and inner suburban ring. Urban densities in these clusters are relatively high, underscoring the favorable conditions for introducing efficient transit service. We conclude that accessibility insufficiency is not merely an issue of far-flung exurbs and the metropolitan fringes, but just as much a problem affecting the large transit reliant population in the urban cores and inner suburban rings. This underscores the possibilities for addressing the issue through increased and targeted investments in high-quality transit systems and transit-corridor urban densification.